2018
DOI: 10.2147/ppa.s152146
|View full text |Cite
|
Sign up to set email alerts
|

“I did not want to take that medicine”: African-Americans’ reasons for diabetes medication nonadherence and perceived solutions for enhancing adherence

Abstract: BackgroundDiabetes is disproportionally burdensome among African-Americans (AAs) and medication adherence is important for optimal outcomes. Limited studies have qualitatively examined reasons for nonadherence among AAs with type 2 diabetes, though AAs are less adherent to prescribed medications compared to whites. This study explored the reasons for medication nonadherence and adherence among AAs with type 2 diabetes and examined AAs’ perceived solutions for enhancing adherence.MethodsForty AAs, age 45–60 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 59 publications
1
64
1
3
Order By: Relevance
“…[ 57 ] In our prior work, AAs’ reasons for intentionally not taking their medicines were associated with their concerns about medication side effects, as well as fear and frustration associated with taking their diabetes medicines. [ 12 ] Managing diabetes is stressful and AAs are fearful and preoccupied with thoughts of future disability, loss of independence, and death. [ 25 , 58 ] Providing behavioral and psychological support that alleviates the distress and emotional toll of diabetes, and offers positive support through family, community and social organizations are needed for AAs with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 57 ] In our prior work, AAs’ reasons for intentionally not taking their medicines were associated with their concerns about medication side effects, as well as fear and frustration associated with taking their diabetes medicines. [ 12 ] Managing diabetes is stressful and AAs are fearful and preoccupied with thoughts of future disability, loss of independence, and death. [ 25 , 58 ] Providing behavioral and psychological support that alleviates the distress and emotional toll of diabetes, and offers positive support through family, community and social organizations are needed for AAs with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 , 9 ] Studies have shown that illness perceptions influence whether patients take their medicines or not, and hence should be taken into account in designing adherence interventions. [ 10 12 ] However, AA patients’ perception of type 2 diabetes is not well understood, and to date, no known studies have used a comprehensive evidence-based theoretical framework to explore what AAs with type 2 diabetes know, believe, and think about type 2 diabetes. Moodley et al, 2000, have called for qualitative studies that use comprehensive theories, since these type of studies are limited among AAs.…”
Section: Introductionmentioning
confidence: 99%
“…However, a relevant proportion of patients do not stop taking medications because they feel worse but because they feel better. Given the plethora of reasons for intentional nonadherence, an individual approach is necessary to positively modulate adherence in elderly people with PD (31,32). Because many people discontinue medication because of side effects, comprehensive education on side effects and what to do in case of side effects is recommended for every patient.…”
Section: Self-reported Reasons For Nonadherencementioning
confidence: 99%
“…Fearing medication and fearing side effects are an important issue for treatment non‐adherence (Harrold & Andrade, ). Among hypertension, diabetes and atopic dermatitis patients, this is significantly associated with poor adherence (Al‐Ramahi, ; Patel & Feldman, ; Shiyanbola, Brown, & Ward, ). Hromadkova et al (), in line with our study, could not detect this association in SSc patients.…”
Section: Discussionmentioning
confidence: 99%